U.S. high school coaches' knowledge, perception, and current practices regarding exertional heat illness - Thompson, B.; Hillman, A. R.; Payne, E. K. (International Sport Coaching Journal, 2024)
Exertional heat illness (EHI) is a dangerous, but preventable and treatable condition that affects approximately 9,000 athletes each year in the United States. Unfortunately, less than 30% of schools in the United States have access to an athletic trainer, making coaches responsible for the safety of the athletes during practices and games. The purpose of this study was to evaluate the knowledge, perception, and procedures of high school coaches in the United States regarding heat illness recognition, prevention, and treatment. An online survey including Likert items and open-ended questions was completed by 1,676 coaches from 16 states and compared between age, coaching experience, gender, education level, experience handling EHI, state, and the completion of either a general coaching certification or a heat safety certification. Average knowledge score among coaches was 74%. Coaches with experience handling or witnessing EHI, more years of coaching experience, older age, and the completion of a coaching certification had significantly higher level of knowledge than others. Results revealed that evidence-based strategies and state mandates aimed at preventing EHI are not being implemented. More training in prevention, recognition, and treatment of EHI is necessary for all individuals involved with high school athletes to prevent avoidable deaths.